2020
DOI: 10.1590/1413-785220202801226897
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Valgus Anatomical Alterations and Its Correlation With the Radiographic Findings

Abstract: Objective: To describe the anatomical and pathological osteoarticular, muscular and tendinous variations in feet of cadavers with hallux valgus and to correlate them with the degree of radiographic deformity. Methods: Dissections and radiographs were conducted in the feet of 22 cadavers with halux valgus, aged between 20 and 70 years. The feet affected were compared with 5 normal feet in order to document the anatomical and pathological, myotendinous and articular variations found. Results: The extensor hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The sesamoids on the head of the rst metatarsal are in dynamic balance because of pulling by two group muscles [31] . So in theory, either sesamoid dislocation could lead to hallux valgus [32][33] .In this study, it was found that the normal position of sesamoid bone (FSP) intersected with the lateral cortex of the rst metatarsal bone accounted for (52.3 ± 3.2) % of the total area of sesamoid bones. The purpose of this study was to nd a quantitative index for judging the dislocation of sesamoid bones on the rst metatarsal head.…”
Section: Correlation Between Tibial Sesamoid Bone and Hallux Valgusmentioning
confidence: 73%
“…The sesamoids on the head of the rst metatarsal are in dynamic balance because of pulling by two group muscles [31] . So in theory, either sesamoid dislocation could lead to hallux valgus [32][33] .In this study, it was found that the normal position of sesamoid bone (FSP) intersected with the lateral cortex of the rst metatarsal bone accounted for (52.3 ± 3.2) % of the total area of sesamoid bones. The purpose of this study was to nd a quantitative index for judging the dislocation of sesamoid bones on the rst metatarsal head.…”
Section: Correlation Between Tibial Sesamoid Bone and Hallux Valgusmentioning
confidence: 73%
“…Hallux valgus is characterized as a combined axial, sagittal, and coronal deformity with a malpositioning of the first metatarsophalangeal joint caused by a lateral deviation of the great toe and a medial deviation of the first metatarsal (Cavalheiro et al 2020; Haines & McDougall 1954; Perera et al 2011). Often, the steps leading to development of HV can occur alongside each other, and are influenced by both intrinsic and extrinsic factors such as genetics, age, metatarsal morphology, and footwear (Perera et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As the insertion of AH, which is expected to strongly resist the valgus of the proximal phalanx and support the medial capsule of the joint in a normal individual, is displaced plantar, the resistance function of this muscle against valgus becomes less e cient [11,54,60]. The placement of the EHL, EHB and FHL tendons relative to the axes of MTPJ shifts laterally as a result of the lateral deviation of the hallux, and it is suggested that this new course of the tendons may increase the severity of the deformity [9,12,34,46]. Although associating these anatomical changes with the degree of radiographic deformity may be important in surgical planning [9], the literature on morphometric de nitions and analysis of positional changes in tendons is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of the EHL, EHB and FHL tendons relative to the axes of MTPJ shifts laterally as a result of the lateral deviation of the hallux, and it is suggested that this new course of the tendons may increase the severity of the deformity [9,12,34,46]. Although associating these anatomical changes with the degree of radiographic deformity may be important in surgical planning [9], the literature on morphometric de nitions and analysis of positional changes in tendons is quite limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation